(3GSJbdGdjI GdHfhc GdeQcRjI Hjf GdeaJQV hGdhGbYs - (3VjGA eLjO(B, (3GdehShjs ((3GdLRGFQ(B:s (3cfhR GdMceI(B,s, 2015)
(3GdHfc GdeQcRj h GdSjGSGJ GdeGdjI h GdfbOjI , GSJbdGdjI GdHfc GdeQcRj , GdHfhc GdeQcRjI LRAG ef GdeTcdI h CjVG LRAG ef GdMd , SjGSI CSJgOGa GdJNVe , SYQ GdUQa h GdSjGSI GdfbOjI , Jehjd GdJLGQI GdNGQLjI(B.s
(3eQGLY U(B.80s
Keywords: (3GdHfhc GdeQcRjIs